Learning with Children in Nature: Documentation as a Cultural Ethic of Plurality - Hall, Claire (Curtin University, 2024)
The ecological identity of young children and their connection to nature is central to their holistic development, yet nature-based learning often lacks acknowledgement in its power to understand the many plural ways in which children learn. Framed within a socio-cultural perspective, this study examined how young children learn as they connect in and with nature to understand the plural and multidimensional child through pedagogical documentation. A qualitative interpretivist epistemology was adopted to explore how complex participatory processes and practices highlight the centrality of the child, with key findings adding knowledge to the relational connection to others and place through pedagogical documentation.